Beta-adrenergic reactivity of erythrocyte membranes in adolescents with supraventricular and ventricular arrhythmias before and after radiofrequency ablation - Т. Yu. Rebrova; Yu. E. Perevoznikova; E. F. Muslimova; L. I. Svintsova; S. A. Afanasiev; O. Yu. Dzhaffarova (Бюллетень сибирской медицины, 2024)
Aim. To evaluate β-adrenergic reactivity of erythrocyte membranes (β-ARM) in adolescents with ventricular and supraventricular arrhythmias before and after radiofrequency ablation (RFA) of heart rhythm disturbances.Materials and methods. The study included 49 adolescents aged 11–17 years, of which 15 had Wolff – Parkinson – White pattern (WPW), 13 – WPW syndrome, 10 – atrioventricular nodal reentry tachycardia (AVNRT), and 11 – ventricular arrhythmia (VA). The control group consisted of 11 adolescents without cardiovascular pathology. All patients received surgical treatment for heart rhythm disturbances (HRD) using RFA. In patients with HRD, β-ARM was determined by a set of reagents BETA-ARM AGAT (AGAT LLC, Russia) before RFA and 3 days after it. In the control group, the parameter was determined at the stage of inclusion in the study.Results. In adolescents with supraventricular arrhythmias, median values of β-ARM did not differ significantly from the control group. RFA in adolescents in these groups did not affect the value of β-ARM on day 3 after the surgery. In adolescents with VA, the median value of β-ARM was initially higher than in the control group (p = 0.026). On day 3 after RFA, an increase in β-ARM was noted in this group (p = 0.028) compared to baseline values.Conclusion. Activation of the sympathetic nervous system plays a significant role in the pathogenesis of VA in adolescence. The study showed the possibility of using β-ARM to assess the state of the sympathetic nervous system in patients with methodological limitations in analyzing heart rate variability.